Singlet Oxygen during Cycling of the Aprotic Sodium–O2 Battery. Issue 49 (2nd November 2017) - Schafzahl, Lukas; Mahne, Nika; Schafzahl, Bettina; Wilkening, Martin; Slugovc, Christian; Borisov, Sergey M.; Freunberger, Stefan A.
Abstract: Aprotic sodium–O2 batteries require the reversible formation/dissolution of sodium superoxide (NaO2 ) on cycling. Poor cycle life has been associated with parasitic chemistry caused by the reactivity of electrolyte and electrode with NaO2, a strong nucleophile and base. Its reactivity can, however, not consistently explain the side reactions and irreversibility. Herein we show that singlet oxygen ( 1 O2 ) forms at all stages of cycling and that it is a main driver for parasitic chemistry. It was detected in‐ and ex‐situ via a 1 O2 trap that selectively and rapidly forms a stable adduct with 1 O2 . The 1 O2 formation mechanism involves proton‐mediated superoxide disproportionation on discharge, rest, and charge below ca. 3.3 V, and direct electrochemical 1 O2 evolution above ca. 3.3 V. Trace water, which is needed for high capacities also drives parasitic chemistry. Controlling the highly reactive singlet oxygen is thus crucial for achieving highly reversible cell operation. Abstract : Parasitic chemistry is the biggest hurdle facing the development of Na–O2 batteries. Evidence is provided that highly reactive singlet oxygen forms at all stages of cycling, especially at high charging voltages, and that it is the main driver for parasitic reactions. Ways to prevent or eliminate singlet oxygen are therefore needed to improve cyclability.